Accuracy and reproducibility of transient elastography for the diagnosis of fibrosis in pediatric nonalcoholic steatohepatitis - Nobili, Valerio; Vizzutti, Francesco; Arena, Umberto; Abraldes, Juan G.; Marra, Fabio; Pietrobattista, Andrea; Fruhwirth, Rodolfo; Marcellini, Matilde; Pinzani, Massimo (Hepatology (Baltimore, Md.), 2008)
Transient elastography (TE) has received increasing attention as a means to evaluate disease progression in chronic liver disease patients. In this study, we assessed the value of TE for the prediction of fibrosis stage in a cohort of pediatric patients with nonalcoholic steatohepatitis. Furthermore, TE interobserver agreement was evaluated. TE was performed in 52 consecutive biopsy‐proven nonalcoholic steatohepatitis patients (32 males, 20 females, age 13.6 ± 2.44 years). The area under the receiver operating characteristic curves for the prediction of “any” (≥1), significant (≥2), or advanced fibrosis (≥3) were 0.977, 0.992, and 1, respectively. Calculation of multilevel likelihood ratios showed that TE values <5, <7, and <9 kPa, suggest the presence of “any” fibrosis, significant fibrosis, and advanced fibrosis, respectively. TE values between 5 and 7 kPa predict a fibrosis stage of 1, but with some degree of uncertainty. TE values between 7 and 9 kPa predict fibrosis stages 1 or 2, but cannot discriminate between these two stages. TE values of at least 9 kPa are associated with the presence of advanced fibrosis. The intraclass correlation coefficient for absolute agreement was 0.961. Conclusion: TE is an accurate and reproducible methodology to identify pediatric subjects without fibrosis or significant fibrosis, or with advanced fibrosis. In patients in which likelihood ratios are not optimal to provide a reliable indication of the disease stage, liver biopsy should be considered when clinically indicated. (HEPATOLOGY 2008.)